2018
DOI: 10.1007/s40273-018-0663-0
|View full text |Cite
|
Sign up to set email alerts
|

Review of Economic Value Drivers of the Treatment of Overactive Bladder

Abstract: Overactive bladder (OAB) is a symptom-driven condition with economic burden estimated to be on the order of several hundred dollars or euros per patient in some North American and European countries. This work reviews recently published economic models to evaluate how health states are defined, what cost components are considered, and what utility values are used to estimate the cost effectiveness of OAB pharmacotherapies, botulinum toxin, or sacral neuromodulation. It was found that no clear standard exists f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Sacral nerve stimulation is an important and effective third‐line therapy in the treatment of overactive bladder symptoms. However, compared to other third‐line treatments, cost is a significant factor to consider with SNS . As such, efforts to help make this therapy more cost effective would increase its potential use for patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Sacral nerve stimulation is an important and effective third‐line therapy in the treatment of overactive bladder symptoms. However, compared to other third‐line treatments, cost is a significant factor to consider with SNS . As such, efforts to help make this therapy more cost effective would increase its potential use for patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, compared to other third-line treatments, cost is a significant factor to consider with SNS. 5,6 As such, efforts to help make this therapy more cost effective would increase its potential use for patients. In this study, we used current Medicare CPT code and APC coding to derive the national average costs for this procedure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our model structure is based on previously published cost-effectiveness models that have been reviewed and deemed acceptable [58]. A review of published economic models evaluating OAB pharmacotherapies found that no standard exists for defining OAB health states, although most include a measure of incontinence frequency like the current study [59]. Other strengths of our model include the quality of the SCORPIO trial data, the inclusion of utilities based on both OAB-5D and EQ-5D instruments, the inclusion of ACB as a factor in the analysis (as mirabegron does not share the ACB associated with antimuscarinic pharmacological OAB treatments), and finally the inclusion of the latest 2017 persistence data for oral OAB therapies [27].…”
Section: Scenario Analysesmentioning
confidence: 99%